Towards an Artificial Phonological Loop: An Assistive Device for Working Memory and Attentional Control - D. Bogen (Applied Bionics and Biomechanics)
We describe the initial development of an artificial phonological loop (APL), a new technology to assist individuals with impairment of the working memory system. The phonological loop, along with the visuospatial sketchpad, is one of the two slave short-term memory subsystems that comprise working memory, a cognitive function closely associated with the control of attention. In the phonological loop, phonological (speech) information lasting for 1–2 second is maintained active by repetitive, subvocal (silent speech) rehearsal. Deficits in working memory, specifically in the phonological loop, occur in many disorders, including attention-deficit disorder and Alzheimer’s disease. In these disorders, it appears that the ability for phonological rehearsal is intact, but the regulation or triggering of the rehearsal process is inadequate, thus causing the contents of working memory to be lost. The purpose, then, of the APL is to facilitate the phonological loop by artificially extending the duration of phonological rehearsals. The APL mimics the natural phonological loop by providing audible vocal echoes to take the place of subvocal rehearsals. In this system, the user talks to him/herself in short (1–2 second) phrases; the device records these phrases, stores them in electronic memory, and then repeats— i.e., echoes—the phrases multiple times over an extended period. Two versions of this device have been developed: the Echo-APL and the Rearticulation-APL. In the Echo-APL, only echoing is involved. In the Rearticulation-APL, however, the user re-vocalizes (rearticulates) the phrase in response to an audible cue. The device repeats the cue until it detects (hears) the re-vocalization. Future research and development of the APL will require extensive testing and careful evaluation of possible echo-schedules: the predefined program controlling inter-echo time intervals and echo-amplitude (echo loudness). The APL essentially exteriorizes the silent phonological loop and makes it audible. It is a system that helps the user to “talk to him/herself” to keep ideas in mind.